2016
DOI: 10.1136/jech-2015-207016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Dutch urban regeneration programme on mental health trends: a quasi-experimental study

Abstract: BackgroundThis paper aims to assess the mental health impact of an urban regeneration programme implemented from 2008 onwards in the 40 most deprived districts in the Netherlands. Interventions varied from improvements in the built environment to activities promoting social cohesion.MethodsWe accessed repeated cross-sectional data from the annual Health Interview Survey, for the period 2004–2011 among adults (n target districts=1445, n rest of the Netherlands=44 795). We used multilevel logistic regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Both scales are designed to measure levels of negative emotional states experienced in the four weeks prior to the interview and are widely used to screen on psychological distress [19]. The K10 categorizes levels of psychological distress in no [10][11][12][13][14][15][16][17][18][19], mild [20][21][22][23][24], moderate [25][26][27][28][29] and severe . The K6 categorizes Levels psychological distress into no [6][7][8][9][10][11] ,mild -moderate [12][13][14][15][16][17][18][19] and severe [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Mental Healthmentioning
confidence: 99%
“…Both scales are designed to measure levels of negative emotional states experienced in the four weeks prior to the interview and are widely used to screen on psychological distress [19]. The K10 categorizes levels of psychological distress in no [10][11][12][13][14][15][16][17][18][19], mild [20][21][22][23][24], moderate [25][26][27][28][29] and severe . The K6 categorizes Levels psychological distress into no [6][7][8][9][10][11] ,mild -moderate [12][13][14][15][16][17][18][19] and severe [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Mental Healthmentioning
confidence: 99%
“…For instance, a tendency towards a more positive trend in mental health in the target districts was found exclusively among female residents and in districts that implemented an intensive regeneration programme [10]. Studies from other countries underwrite the need for subgroup analyses [1618,21].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of GoWell housing regeneration in Glasgow found that reductions in health inequalities were confined to ‘higher investment areas’ 35. Mental health improvements achieved through the Dutch District Approach were limited to districts that implemented more intensive programmes 29. The Well London initiative only found tentative evidence of progress on some health outcomes in ‘higher exposure areas’ 31 36.…”
Section: Discussionmentioning
confidence: 99%